Very low oral exposure to prions of brain or saliva origin can transmit chronic wasting disease. - Nathaniel D Denkers; Clare E Hoover; Kristen A Davenport; Davin M Henderson; Erin E McNulty; Amy V Nalls; Candace K Mathiason; Edward A Hoover (PLoS ONE, 2020)
The minimum infectious dose required to induce CWD infection in cervids remains unknown, as does whether peripherally shed prions and/or multiple low dose exposures are important factors in CWD transmission. With the goal of better understand CWD infection in nature, we studied oral exposures of deer to very low doses of CWD prions and also examined whether the frequency of exposure or prion source may influence infection and pathogenesis. We orally inoculated white-tailed deer with either single or multiple divided doses of prions of brain or saliva origin and monitored infection by serial longitudinal tissue biopsies spanning over two years. We report that oral exposure to as little as 300 nanograms (ng) of CWD-positive brain or to saliva containing seeding activity equivalent to 300 ng of CWD-positive brain, were sufficient to transmit CWD disease. This was true whether the inoculum was administered as a single bolus or divided as three weekly 100 ng exposures. However, when the 300 ng total dose was apportioned as 10, 30 ng doses delivered over 12 weeks, no infection occurred. While low-dose exposures to prions of brain or saliva origin prolonged the time from inoculation to first detection of infection, once infection was established, we observed no differences in disease pathogenesis. These studies suggest that the CWD minimum infectious dose approximates 100 to 300 ng CWD-positive brain (or saliva equivalent), and that CWD infection appears to conform more with a threshold than a cumulative dose dynamic.